2017
DOI: 10.1097/qad.0000000000001574
|View full text |Cite
|
Sign up to set email alerts
|

HIV-hepatitis B virus coinfection

Abstract: HIV infection has a significant impact on the natural history of chronic HBV infection, with increased levels of HBV DNA, accelerated progression of liver disease and increased liver-associated mortality compared to HBV mono-infection. Widespread uptake and early initiation of HBV-active antiretroviral therapy (ART) has substantially improved the natural history of HIV-HBV co-infection but the prevalence of liver disease remains elevated in this population. In this paper, we review recent studies examining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(104 citation statements)
references
References 223 publications
(145 reference statements)
5
97
0
2
Order By: Relevance
“…It is estimated that approximately 7.4% of PLWH are chronically HBV infected; conversely, about 1% of those with chronic HBV infection are HIV infected [14]. Coinfection rates are geographically heterogeneous and vary from 5% to up to 20% worldwide, depending on various factors such as distribution of risk groups, implementation of HBV vaccination programs, and levels of endemicity in the general population [15][16][17]. The highest rates are found in Asia and Africa [18], primarily affecting vulnerable populations of low-/middle-income countries [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that approximately 7.4% of PLWH are chronically HBV infected; conversely, about 1% of those with chronic HBV infection are HIV infected [14]. Coinfection rates are geographically heterogeneous and vary from 5% to up to 20% worldwide, depending on various factors such as distribution of risk groups, implementation of HBV vaccination programs, and levels of endemicity in the general population [15][16][17]. The highest rates are found in Asia and Africa [18], primarily affecting vulnerable populations of low-/middle-income countries [19].…”
Section: Introductionmentioning
confidence: 99%
“…The natural history of HBV is complicated by HIV coinfection. Patients have an increased risk of death and progression to liver cirrhosis [16,18,23,24]. The negative impact of HIV/ HBV includes higher HBV replication levels and higher risk of chronic infection or reactivations, and progress to liver cirrhosis and hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of chronic HBV HIV co-infection differs among regions as well as risk based groups [21]. Several studies have been conducted in Europe on the…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Studies have reported that the prevalence of co-infection between HIV and HBV in the general population ranges from 5% to 20%, but that in PWIDs it is just under 30% (Singh et al, 2017;Thio et al, 2002). As with other diseases, HBV/HIV coinfection is common, causing a greater risk of developing liver cirrhosis and hepatocellular carcinoma, with up to sixfold progressions of liver disease (Sulkowski, Thomas, Chaisson, & Moore, 2000).…”
Section: Suds and Their Relationship With Hiv And Other Stismentioning
confidence: 99%